015 Long-term (1-year) seizure freedom with adjunctive perampanel in paediatric patients with epilepsy: study 311. Issue 6 (27th May 2022) - Flamini, Robert; Patten, Anna; Malhotra, Manoj; Ngo, Leock Y
Abstract : Background: Long-term (1-year) seizure-freedom rates with adjunctive perampanel were assessed in paediatric patients aged 4–<12 years with focal-onset seizures (FOS) (with/without focal to bilateral tonic-clonic seizures [FBTCS]) or generalised tonic-clonic seizures (GTCS) during Study 311 (NCT02849626 ). Methods: Seizure-freedom rates (FOS, FBTCS, GTCS) were assessed in patients who achieved seizure freedom during the Core Study Maintenance Period and then remained seizure free for up to 12 months (calculated from the start of their seizure-free period). Data were stratified by concomitant enzyme- inducing anti-seizure medications (EIASMs) (with and without) and age (4–<7 and 7–<12 years). Results: For FOS, 6/11 (54.5%) patients remained seizure free for 12 months (with EIASMs, n=2/5 [40.0%]; without EIASMs, n=4/6 [66.7%]; 4–<7 years, n=0/1; 7–<12 years, n=6/10 [60.0%]). For FBTCS, 1/5 (20.0%) patient(s) remained seizure free for 12 months (with EIASMs, n=0/1; without EIASMs, n=1/4 [25.0%]; 4–<7 years, n=0/2; 7–<12 years, n=1/3 [33.3%]). For GTCS, 3/7 (42.9%) patients remained seizure free for 12 months (all 7–<12 years, n=3/6 [50.0%]; no GTCS seizure-free patients received EIASMs). Conclusion: Despite small patient numbers, seizure-freedom rates are maintained during long-term (1-year) perampanel treatment in paediatric patients, consistent with analyses in adolescents/adults. Funding.Eisai Inc. stella_ngo@eisai.com